2013
DOI: 10.1038/srep02016
|View full text |Cite
|
Sign up to set email alerts
|

Superconductivity in Topological Insulator Sb2Te3 Induced by Pressure

Abstract: Topological superconductivity is one of most fascinating properties of topological quantum matters that was theoretically proposed and can support Majorana Fermions at the edge state. Superconductivity was previously realized in a Cu-intercalated Bi2Se3 topological compound or a Bi2Te3 topological compound at high pressure. Here we report the discovery of superconductivity in the topological compound Sb2Te3 when pressure was applied. The crystal structure analysis results reveal that superconductivity at a low… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
91
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 144 publications
(98 citation statements)
references
References 36 publications
5
91
2
Order By: Relevance
“…The DAC technique coupled with a hydrostatic pressure medium (Fig. 1b) has been shown to be effective in elucidating the electrical, vibrational, optical and structural properties of a plethora of materials 21,[23][24][25] . The optically transparent window of the diamond allows us to conduct a series of in situ highpressure experiments including accurate pressure calibration from ruby fluorescence, electrical transport measurements and optical Raman and synchrotron X-ray diffraction (XRD) spectroscopy 26 , leading to the observation of S-M transition in multilayered MoS 2 at high pressures.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The DAC technique coupled with a hydrostatic pressure medium (Fig. 1b) has been shown to be effective in elucidating the electrical, vibrational, optical and structural properties of a plethora of materials 21,[23][24][25] . The optically transparent window of the diamond allows us to conduct a series of in situ highpressure experiments including accurate pressure calibration from ruby fluorescence, electrical transport measurements and optical Raman and synchrotron X-ray diffraction (XRD) spectroscopy 26 , leading to the observation of S-M transition in multilayered MoS 2 at high pressures.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, previous theoretical studies have suggested that an iso-structural semiconducting to metallic (S-M) transition in multilayered MoS 2 can be induced by pressure or strain [18][19][20] . Despite the broad interest in this phenomenon in layered nanomaterials, previous experimental results only reported a limited reduction in the electrical resistance 17,[21][22][23] with no clear evidence for the pressureinduced S-M transition.…”
mentioning
confidence: 95%
“…The linear temperature dependence of H c2 in Figure 3b is actually very interesting. It may come from a two-band Fermi surface topology as in MgB 2 , [35][36][37] or an unconventional superconducting state as in heavy-fermion compound UBe 13 . 38 11,[39][40][41] We notice that no superconductivity was observed up to 13.43 GPa in an earlier pressure study of Cd 3 As 2 single crystal.…”
Section: Pressure-induced Superconductivitymentioning
confidence: 99%
“…7,8 Under pressure, Bi 2 Te 3 , Bi 2 Se 3 , Sb 2 Te 3 and Sb 2 Se 3 become superconducting, which are also regarded as candidates for TSCs. [9][10][11][12][13][14] Note that there are debates on whether these candidates are indeed TSCs, [9][10][11][12][13][14][15][16][17] therefore further experimental works are needed to definitely identify a TSC and manipulate the Majorana fermions on its surface.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation